Pelatihan Pembuatan Bakso guna Meningkatkan Sumber Pendapatan Wali Santri Panti Asuhan Tahfidz Hidayah Sukadamai Kabupaten Bogor - Ahmad Haetami; Maskhur Dwi Saputra; Sugeng Riyadi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aimed to improve the economic independence of parents or guardians of students at the Tahfidz Hidayah Orphanage in Sukadamai, Bogor, West Java, through a meatball-making training program. The program was carried out in three stages: planning, implementation, and evaluation. The planning stage involved site surveys, scheduling, and coordination of facilities. The implementation stage covered entrepreneurship education, demonstrations by the training team, and hands-on practice with emphasis on hygiene standards and product quality. Results from the evaluation stage showed an average product score of 86.66, placing participant performance in the good category. Questionnaire data further confirmed that the instructional materials were easy to follow, the demonstrations were well-structured, and the available facilities were sufficient to support the training activities. This practice-based training proved effective in building participants' technical competence and strengthening their motivation to pursue independent entrepreneurial ventures.